2007
DOI: 10.1080/10408440601177780
|View full text |Cite
|
Sign up to set email alerts
|

Grey Gooon the Skin? Nanotechnology, Cosmetic and Sunscreen Safety

Abstract: Many modern cosmetic or sunscreen products contain nano-sized components. Nanoemulsions are transparent and have unique tactile and texture properties; nanocapsule, nanosome, noisome, or liposome formulations contain small vesicles (range: 50 to 5000 nm) consisting of traditional cosmetic materials that protect light-or oxygen-sensitive cosmetic ingredients. Transdermal delivery and cosmetic research suggests that vesicle materials may penetrate the stratum corneum (SC) of the human skin, but not into living s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
347
0
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(365 citation statements)
references
References 113 publications
2
347
0
16
Order By: Relevance
“…Skin hair follicles are surrounded by a tight network of capillaries (Fig. 4), which facilitates transdermal drug delivery [49] but also provides a possible route for NP entry and a long-term NP reservoir. Although only 1% of applied TNPs were found in the orifices of hair follicles, these deposits were much harder to remove than those on the skin surface [45][46][47][48].…”
Section: Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin hair follicles are surrounded by a tight network of capillaries (Fig. 4), which facilitates transdermal drug delivery [49] but also provides a possible route for NP entry and a long-term NP reservoir. Although only 1% of applied TNPs were found in the orifices of hair follicles, these deposits were much harder to remove than those on the skin surface [45][46][47][48].…”
Section: Skinmentioning
confidence: 99%
“…So far, there is no evidence that NP skin penetration leads to systemic exposure. Most studies have found that TNPs remain at the outmost layer of stratum corneum, possibly in skin furrows or the infundibulum; little TNP has been found in the living epidermis [49,[51][52][53][54][55][56]. Moreover, acute dermal irritation studies and local lymph node assays in mice found no irritation or sensitization [57].…”
Section: Skinmentioning
confidence: 99%
“…Furthermore, ZnO as a bio safe compound is found to be useful in applications linked to human life, such as in cosmetic, medical, and dental products [1,2]. It has become one of the most promising compounds that can be employed in advance technology applications, and it demonstrates outstanding performance in various application fields, such as sensors for different analytics including those for hydrogen, oxygen, Volatile organic compounds (VOCs) [3][4][5], urea, cholesterol, and glucose [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It also deals with the quantitative evaluation of severity and frequency of nanotoxic effects in relation to the exposure of the organisms. Metal nanoparticles have been used in various fields such as consumer products, industrial applications and health care technology are likely to enter the environment (Masciangioli and Zhang 2003;Nohynek et al 2007;Benn and Westerhoff 2008) stated that the AgNPs are commonly used in the textiles and these nanoparticles might be released into the environment. The toxicological evidence of AgNPs is still lacking and the safety measurements for these nanoparticles have to be framed.…”
Section: Introductionmentioning
confidence: 99%